Studi Molecular Docking Senyawa Turunan Benzotiazol Berbasis Oksadiazol sebagai Inhibitor Aldose Reductase - Ali Farisan Qisthi; Fitri Amelia (Lembaga Yasin AlSys, 2026)
Diabetes mellitus is a chronic metabolic disease that can cause various complications, such as neuropathy, retinopathy, and nephropathy, due to sorbitol accumulation through the polyol pathway. The aldose reductase enzyme plays an important role in this process and is therefore a potential therapeutic target in preventing diabetes complications. This study aimed to evaluate the potential of oxadiazole-based benzothiazole derivative compounds as aldose reductase inhibitors through molecular docking studies and pharmacokinetic analysis. This study was conducted in silico using Molecular Operating Environment (MOE) 2019.0102 software. Molecular docking simulations were performed on the aldose reductase protein (PDB ID: 4JIR) and then analyzed based on binding affinity values, RMSD, ligand–protein interactions, and evaluation of Lipinski’s Rule of Five using SwissADME. The docking validation results showed an RMSD value of 1.279 Å, indicating that the docking method used was valid. The docking results showed that all ligands had good binding energy values in the range of −7.97 to −8.81 kcal/mol. Compounds 1j, 1m, 1d, 1o, and 1n showed the best binding affinity and stable interactions with important residues, such as ASP43, TRP111, TYR209, and SER210. Pharmacokinetic evaluation showed that most compounds met Lipinski’s Rule of Five, indicating good drug-likeness properties. The conclusion of this study emphasizes that oxadiazole-based benzothiazole derivative compounds have the potential to be developed as aldose reductase inhibitor candidates to support further development of antidiabetic therapy. These findings imply the use of an in silico approach as an initial strategy for more efficient screening of antidiabetic compound candidates.